PAPARA'S HOLE (PANGEEA, 2025)
Papara's Hole - Huda lui Papară - is one of the most famous and important caves in Romania and Europe, being situated in the northern Carpathians. It has long been known since prehistory, but its exploration began in the 80's of the last century by members of the Speleology Circle in the town of Blaj (Alba County, Romania), who made the first touristic arrangement cave. This paper presents a cave history that blends with a set of legends that have been created around it and have had a strong impact on the local community. It is then presented the entire evolution of the cave exploration and arrangement, which no longer exists, due to floods that destroyed the settlement in time.
Keywords: hole; Ancient History; exploration; the layout of the cave